2019
DOI: 10.1111/nyas.14204
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image, Volume 1448, Issue 1

Abstract: On the back cover: From Zhongqiang Li et al., “Indocyanine green‐assisted dental imaging in the first and second near‐infrared windows as compared with X‐ray imaging.” https://doi.org/10.1111/nyas.14086.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…10,13 In our previous pilot studies, we demonstrated the feasibility of ICG-NIRF dental imaging based on both a rat model 40,41,44 and human extracted teeth. 42,43 These results showed the promise of using ICG-NIRF dental imaging for crack detection. In our study here, we investigate the effectiveness of ICG-NIRF imaging to detect cracked teeth in the first and second NIR windows and to estimate crack depth from these images.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…10,13 In our previous pilot studies, we demonstrated the feasibility of ICG-NIRF dental imaging based on both a rat model 40,41,44 and human extracted teeth. 42,43 These results showed the promise of using ICG-NIRF dental imaging for crack detection. In our study here, we investigate the effectiveness of ICG-NIRF imaging to detect cracked teeth in the first and second NIR windows and to estimate crack depth from these images.…”
Section: Discussionmentioning
confidence: 79%
“…The imaging platform, as used in our previous studies, 42,43 consists of NIR light sources (785 nm and 1300 nm laser sources) and NIR cameras. A bifurcated optical fiber is connected to the laser sources and is used to guide the laser light to expose the tooth samples.…”
Section: Icg-nirf Dental Imaging Platformmentioning
confidence: 99%
See 3 more Smart Citations